Computational Assessment of Water Desalination Performance of Multi‐Walled Carbon Nanotubes. Issue 4 (24th February 2020) - Ghoufi, Aziz; Szymczyk, Anthony
Abstract: The desalination performance (water permeability and salt rejection) of both uncharged and charged multi‐walled carbon nanotubes (MWCNTs) is computationally assessed by means of pressure‐driven molecular dynamics simulations. It is shown that the performance of these materials surpass that of the widely used polyamide reverse osmosis membranes and are even better than 2D materials such as nanoporous graphene or boron nitride. The molecular origin of the fast water transport through MWCNT materials is ascribed to a synergic effect between the existence of a single water layer and low friction between water molecules and the carbon nanotube surface. Furthermore, for charged MWCNTs it is highlighted that the electrical charges on the nanotube surface result in a strong anchoring of ions and water molecules. This leads to clogging of the annular region between nanotubes and the generation of a force, which makes water transport through the central channel of the MWCNT faster. Abstract : The desalination performance of uncharged and charged multi‐walled carbon nanotubes is computationally investigated. The performance of these materials surpasses that of the widely used polyamide reverse osmosis membranes and is even better than nanoporous graphene. The clogging of the annular region between nanotubes generates an axial thrust, improving water permeability and salt rejection.